BIOFUELS: AN ALTERNATIVE TO OIL? - ROTH, Andrei (Studia Universitatis Babes-Bolyai Studia Europaea, 2015)
Oil dominates our world energetic mix and this aspect is especially visible in the transportation sector with over 90% of the fuel supply being represented by oil. Due to the geographic concentration of oil reserves, assuring energetic security becomes a challenge for countries short of resources. Biofuels are liquid or gaseous fuels derived from biomass. Energy crops can be specially harvested for this purpose and thus a renewable resource is available. Due to climate change considerations, biofuels use can reduce GHG emissions. Originating from agricultural feedstocks biofuels can offer an alternative market for these commodities. Governments have developed biofuels instruments, such as blending mandates, in order to improve their energetic security, replace oil and maintain the agricultural feedstock prices. The present paper analyzes the opportunity of using biofuels regarding their sustainability, competitiveness and their potential to improve energetic security.